A Coronavirus in the Arab Media: A Transitivity Analysis of Aljazeera Arabic Website - Asim Mahdi , Al- Hilali; Dua'a Hafidh Hussein, L: (lark, 2021)
The present paper approaches the topic of the current study eclectically by adopting critical discourse analysis(CDA), systemic functional linguistics(SFL) and corpus linguistics to show how the present crisis of coronavirus(covid19) is presented in the Arab media, a report in Al-Jazeera as a case study. Through the application of CDA and SFL, the researcher would be able to figure out the ideology and attitudes adopted by this TV channel . Mainly, the concern of the study is to illustrate what types of verb processes are utilized in the report in order to give an account of the way the novel corona pandemic as a participant is introduced and described and what roles are assigned to it. After carrying out an analysis , it is concluded that to reflect the influential and powerful effect that the disease brought about, the writer of the report opted for investing the frequent use of the type of material process verbs to demonstrate actions and events in which Coronavirus is the major actor or agent. Besides, the report`s discourse structures are intentionally selected not to convey the writer`s sentimental attitudes but to inform and emotionally involve the reader in the text interactions .